Investigating pottery production and consumption patterns at the Late Mycenaean cemetery of Perati - Lis, Bartłomiej; Mommsen, Hans; Maran, Joseph; Prillwitz, Susanne (Journal of archaeological science reports, 2020)
The large assemblage of well-preserved pottery from the extensive Late Bronze Age cemetery at Perati in East Attica (Greece) lends itself to a case study for investigating patterns of production and consumption of Mycenaean pottery. This article presents the chemical characterization by NAA of 28 pottery samples from Perati combined with a definition of ceramic macroscopic groups. The set of samples from all three chronological stages of the cemetery covers the two prevalent macroscopic groups, the presumably local standard fabric and the commonly present so-called White Ware, a distinctive pottery group known from other sites in Greece, but rarely subjected to scientific analyses. The two main NAA groups, PerA and PerC, correlate well both with the standard fabric and with the White Ware. These groups may indicate one or more local/regional workshop(s), products of which are found only occasionally at other sites included in the Bonn database. In addition to imports with chemical patterns pointing to Central Crete and Chios, several chemical singletons have been identified. Overall, the analyses show predominant consumption of local pottery, with a limited presence of imports.